Strategi Pemasaran Dalam Rangka Meningkatkan Penjualan Benq Interactive Flat Panel - Mike Avelinus Thendry dan Anas Lutfi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Technological developments currently occur in several fields such as technological developments in the field of presentation. The latest presentation technology today is by using interactive flat panel where with this technology can provide a very good experience to its users. The purpose of the research is to obtain a description of marketing strategic steps that should be done by PT Datascrip in an effort to increase sales from Benq interactive flat panel and assess the extent to which the effectiveness of marketing strategies applied. The method used in this research is by qualitative descriptive method and by doing SWOT analysis (EFE and IFE matrix). The results of the EFE and IFE matrix analysis show that BenQ interactive flat panel products in overcoming threats are above average or show that BenQ interactive flat panel products have the ability to reach existing opportunities and internal management of PT Datascrip has strong enough capital to compete with competitors. The conclusion of this research is marketing strategy that can be done that is market development strategy, market penetration, and product development.